Development of DelTalk (an English learning application) using Agile Method - Tegar Arifin Prasetyo; Monalisa Pasaribu; Tiurma Lumban Gaol; Togu Novriansyah Turnip; Juli Yanti Damanik; Andree Panjaitan; Mei Pane; Nathan Fernando Lumban Tobing; Lilis Marito Pardosi; Timothy Timothy; Yohana Sihombing (Universitas Negeri Padang, 2023)
English has become a world language that must be mastered by many people because English has dominated the era of communication to connect and transfer knowledge to the entire world. When it comes to the development of mobile applications for language learning, previous research has tended to emphasize testing on various technologies such as multimedia, virtual and augmented reality, conversational agents and artificial intelligence-based systems. This research, therefore, aimed to develop a mobile-based English learning application that provided English learning in the form of stories called the Deltalk. This mobile-based English learning application provides features in which the users can practice their speaking in English. This app was developed by integrating ASR (Automatic Speech Recognition) technology provided by NOVO Learning. The ASR was integrated with Deltalk through the API (Application Programming Interface) and Websocket. Deltalk development adapted two agile frameworks, including Scrum and Lean Software Development by performing MVP process one time.